Відповідність принципів забезпечення складникам системи забезпечення розвитку внутрішнього ринку товарів, систематизація і групування її властивостей - Мардус, Наталія Юріївна (Міжнародний гуманітарний університет, 2018)
Досліджено відповідність принципів забезпечення складовим частинам системи забезпечення розвитку внутрішнього ринку товарів. Визначено, що споживча частина системи являє собою об'єкт забезпечення, яким виступає розвиток внутрішнього ринку товарів. Установлено, що серед активних частин системи формуючій частині відповідають загальні принципи побудови систем, тоді як реалізуючій та підтримуючій частинам – принципи процесу забезпечення. Визначено ключові властивості системи, у результаті чого отримано систематизацію та групування властивостей системи й установлено, що поділ властивостей системи забезпечення залежить від того, яка складова частина їх генерує.

The question of forming a system for ensuring the internal market of goods is in line with the principles of ensuring the components of the system for ensuring the development of the internal market of goods. When forming a system for ensuring the internal market of goods, they define the inherent system of integrated properties that build the essential links of the system. The conformity of the principles of ensuring the components of the system for ensuring the development of the internal market of goods is studied. It is determined that the consumer part of the system is an object of support, which supports the development of the domestic market of goods. It has been established that among the active parts of the forming part of the system, the general principles of system building correspond to the general principles, while the implementing and supporting parts are the principles of the assurance process. The researches of different scientists and the key features of the system are analyzed. As a result of the study, the properties of the system of security are grouped into two groups – properties generated by separate elements (component parts) of the system for ensuring the development of the internal market of goods, as well as system-wide properties that arise as a result of the interaction between these elements. As a result of the study systematization and grouping of system properties were obtained. It has been established that the separation of the properties of the system of security depends on which component it generates.
Correspondence of the principles of ensuring the components of the system ensuring the development of the internal market of goods, the systematization and grouping of its properties
Keywords: внутрішній ринок товарів; ринок товарів; система забезпечення розвитку; об'єкт забезпечення